2011
DOI: 10.1016/j.ajhg.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Null Mutations of MSRB3 Encoding Methionine Sulfoxide Reductase Are Associated with Human Deafness DFNB74

Abstract: The DFNB74 locus for autosomal-recessive, nonsyndromic deafness segregating in three families was previously mapped to a 5.36 Mb interval on chromosome 12q14.2-q15. Subsequently, we ascertained five additional consanguineous families in which deafness segregated with markers at this locus and refined the critical interval to 2.31 Mb. We then sequenced the protein-coding exons of 18 genes in this interval. The affected individuals of six apparently unrelated families were homozygous for the same transversion (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
75
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 47 publications
0
75
0
1
Order By: Relevance
“…MSRB2 overexpression protects human cells from H 2 O 2 -induced oxidative damage, generation of ROS, loss of mitochondrial membrane potential, protein carbonyl accumulation and apoptotic cell death, thus ensuring the mitochondrial integrity and cell survival by scavenging ROS [131]. The autosomal recessive null mutations in the human MSRB3 have been implicated in mitochondrial dysfunction leading to deafness (DFNB74 MIM:613718 [132]). …”
Section: (A) Protein Repair By Reduction Of Oxidized Proteinsmentioning
confidence: 99%
“…MSRB2 overexpression protects human cells from H 2 O 2 -induced oxidative damage, generation of ROS, loss of mitochondrial membrane potential, protein carbonyl accumulation and apoptotic cell death, thus ensuring the mitochondrial integrity and cell survival by scavenging ROS [131]. The autosomal recessive null mutations in the human MSRB3 have been implicated in mitochondrial dysfunction leading to deafness (DFNB74 MIM:613718 [132]). …”
Section: (A) Protein Repair By Reduction Of Oxidized Proteinsmentioning
confidence: 99%
“…A previous study reported that mutations in the MSRB3 gene cause autosomal recessive hearing loss [Ahmed et al, 2011]. In addition, we recently reported that MsrB3 protein is expressed in sensory epithelia in the cochlea and vestibular tissue of the mouse, and that loss of MsrB3 in mice led to profound hearing loss due to hair cell apoptosis [Kwon et al, 2014].…”
mentioning
confidence: 99%
“…The cochlear expressions of MsrA in the cells of the spiral ganglion, Corti cells, and the lateral wall have suggested that the presence of MsrB and MsrA in these structures can prevent cochlear damage as a result of oxidative stress [Ahmed et al, 2011;Kwon et al, 2014b]. The loss of cells in the organs of Corti, spiral ganglion, and lateral wall has been reported in hearing loss studies [Fernandez et al, 2015;Hequembourg and Liberman, 2001;Ng et al, 2015].…”
Section: Mechanisms Of Msr-mediated Protection In the Inner Earmentioning
confidence: 98%
“…Studies on the roles of the Msrs on cochlear protection have been limited. Mutations of the MsrB3 gene are normally linked to autosomal recessive prelingual individual deafness; these mutations are associated with the protein-reducing capability of methionine sulfoxide [Ahmed et al, 2011]. In this experiment, the ablation of the MsrB3 in mice stimulated apoptotic death of the cells in the inner part of the ear; there was also disintegration of the stereocilia of hair cells inside the ear, and deafness was determined by 20 days of age [Kwon, et al, 2014a].…”
mentioning
confidence: 92%